2015
DOI: 10.1055/s-0035-1570088
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Complications of Pedicle Subtraction Osteotomy

Abstract: Study Design Retrospective case series. Objective To describe the perioperative complications (0 to 90 days) associated with pedicle subtraction osteotomies (PSOs) performed at a tertiary spine center by two experienced spine surgeons who recently adopted the technique. Methods We reviewed all 65 patients (47 women and 18 men; mean age 60 years, range 24 to 80) who underwent a PSO at our institution. Descriptive data and analysis of complications were limited to the perioperative time (within 90 days of surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 18 publications
2
22
1
1
Order By: Relevance
“…Other authors have looked at outcomes of PSO in the lumbar spine in the treatment of large sagittal deformities of the lumbar spine. In the literature, PSO complications are generally analyzed as 2 tipes: minor or major complication [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…Other authors have looked at outcomes of PSO in the lumbar spine in the treatment of large sagittal deformities of the lumbar spine. In the literature, PSO complications are generally analyzed as 2 tipes: minor or major complication [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…2,4 Their use is only justified because sagittal correction is of great importance in the context of adult deformities, since it has been shown that pain and disability are directly related to an increased SVA and changes in sagittal spinopelvic parameters. [13][14][15] When considering a three-column osteotomy, the decision making process should take the possibility of not achieving sufficient correction or of having postoperative loss of correction into account, [5][6][7][8] since the procedure is subject to various complications and mechanical failures, and may also be impacted by reinterventions that may occur.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Their use is justified by the importance of sagittal correction in surgeries for deformity, but few articles describe how much of this correction is maintained because of complications that occur and the duration of follow-up in these cases. 5,6 This study surveys the mechanical complications and the evolution of sagittal spinopelvic measurements of a series of 20 patients with sagittal imbalance who underwent three-column osteotomies with follow-up for at least one year.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eine Studie von Daubs. et al [44] berichtet über eine Komplikationsrate innerhalb der ersten 3 Monate nach erfolgter PSO von 31 %. Eine weitere Studie von Bridwell et al [45] berichtet über 20 "early-onset" und 12 "late-onset" Komplikationen bei 66 Patienten, welche eine PSO der Lendenwirbelsäule erhielten.…”
Section: Operative Versorgung Und Managementunclassified